Analisis Sistem Penentuan Kelayakan Penerimaan Bantuan Operasional Sekolah (BOS) Menggunakan Metode Simple Additive Weighting - Maulia Ibsanti, Novia Hasdyna, Zakial Vikki, T Irfan Fajri (LPPM-UNIKI, 2021)
School Operational Assistance is a grant provided from the government to carry out teaching and learning activities, so as to reduce the cost burden for students. In data management at the State School 15 Muara Dua Lhokseumawe which still uses the Excel application, it can provide obstacles for the selectors in assessing, several obstacles such as inaccurate and non-transparent data management can occur with existing requirements, so that the process of selecting beneficiaries for students is wrongly targeted. and takes a long time, thus a Decision Support System is needed. Decision Support System (DSS) is a specific information system that is intended to assist management in making decisions related to semi-structured problems effectively and efficiently, and does not choose the decision-making function in making decisions. The Decision Support System implemented in this study uses the Simple Additive Weigting (SAW) method. The purpose of this research is to provide convenience in targeting the process of selecting the right beneficiaries and being more transparent. The results of the research are the application of a decision support application in determining the acceptance of Web-Based School Operational Assistance.